Anaesthetic Management of Cerebral Aneurysm Surgery - Shrestha, Raju (Eastern Green Neurosurgery, 2019)
Management of cerebral aneurysm is always a challenge for a neurosurgeon and anaesthesiologist. Proper knowledge, experience, timely intervention and goal directed therapy will definitely save a lot of lives. The leading causes of death and disability were, in descending order, vasospasm, the direct effects of the initial bleed (massive subarachnoid, subdural, or intracerebral hematoma, permanent ischemic effects of increased intracranial pressure, rebleeding, and surgical complications. This article revises the anaesthetic challenges during managing the cerebral aneusysms.